Anti-Termite Activity of Melia azedarach Extracts - Yanico Hadi Prayogo; Romi Irka Putra; Izza Firdausi Hadiyanto; Evie Nihayah; Wasrin Syafii; Rita Kartika Sari; Irmanida Batubara (Jurnal Sylva Lestari, 2022)
Natural preservatives have been widely considered as non-synthetic materials that can prevent the biodegradation of wood due to subterranean termite attacks, namely Coptotermes curvignathus. Melia azedarach is a fast-growing species that has been widely studied for its antifeedant compounds and shows good potential to be developed as a biopesticide, especially as an anti-termite. This study aimed to identify the termicide and antifeedant properties of the wood, leaves, and bark extracts of Melia azedarach against subterranean termites and identify their bioactive compounds. The acetone extract from the three parts of the tree was fractionated. The most active fractions were selected from each part based on the percentage of termite mortality and antifeedant activity and analyzed for its bioactive compounds by pyrolysis GCMS. The ethyl acetate fraction of Melia azedarach bark exhibited strong toxic properties compared to other fractions. In the leaf section, the diethyl ether fraction showed the best termite repellent (antifeedant) properties. The anti-termite properties influenced phenolic compounds and organic acid that dominated the bark ethyl acetate fraction and leaf diethyl ether fraction. These findings show the great potential of bioactive compounds from biomaterials to be developed as a promising biopesticide. Keywords: anti-termite, bioactive compound, Melia azedarach, natural preservative